Child sexual abuse consequences: a review of intervening variables - Cantón-Cortés, David; Cortés, María Rosario (Anales de Psicología / Annals of Psychology, 2015)
Over the last few decade child sexual abuse (CSA) have provoked a great deal of interest, both among the scientific community and the society, due to its prevalence and short and long term consequences. Although most of the studies examining CSA sequelae list numerous psychological, social, behavioral and physical difficulties, certainly not every child abuse survivor shows a significant harm thereafter, existing a great variability on the survivor´s adjustment. In light of this diversity the present work, after review the short and long term consequences of CSA, attempt to discern which are the main variables that determine the effects of the abuse on the survivors. Characteristics of the abuse, survivor and perpetrator, situational factors and, specially, survivor´s cognitive variables have been proved as efficient in order to explain the symptomatology severity. Specifically, studies have found that replacing avoidance coping strategies by approaching ones, eliminating self-blame and family blame attributions and the four traumagenic dynamics feelings, as well as promoting a secure attachment style would have a positive impact in order to prevent future problems caused by the experience of abuse.